2021
DOI: 10.3390/life11020096
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics of Dry Versus Reanimated Antarctic Lichen-Dominated Endolithic Communities

Abstract: Cryptoendolithic communities are almost the sole life form in the ice-free areas of the Antarctic desert, encompassing among the most extreme-tolerant organisms known on Earth that still assure ecosystems functioning, regulating nutrient and biogeochemical cycles under conditions accounted as incompatible with active life. If high-throughput sequencing based studies are unravelling prokaryotic and eukaryotic diversity, they are not yet characterized in terms of stress adaptations and responses, despite their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…In addition, Coleine et al [13] and Fanelli et al [14] reported two examples of MS-based analyses of microbial communities colonising Antarctic rocks, comparing the metabolic responses of Antarctic endolithic communities when dormant, and after reanimation by wetting, light, and optimal temperature. NMR spectroscopy allowed for metabolomic analysis of soils from agricultural systems or native soils.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Coleine et al [13] and Fanelli et al [14] reported two examples of MS-based analyses of microbial communities colonising Antarctic rocks, comparing the metabolic responses of Antarctic endolithic communities when dormant, and after reanimation by wetting, light, and optimal temperature. NMR spectroscopy allowed for metabolomic analysis of soils from agricultural systems or native soils.…”
Section: Introductionmentioning
confidence: 99%
“…Recently metabolomics was successfully applied to Antarctic cryptoendolithic lichen-dominated communities, defining their adaptation strategies to survive in these harshest conditions. For this reason, metabolomics become a powerful tool to study life in extreme environments ( Coleine et al, 2020 ; Fanelli et al, 2021 ). Here, this approach allows us to investigate (i) which fungal biomolecule maintains their stability after exposure to SVTs, and (ii) the effects of the interactions of two Martian regolith analogues on fungal growth as well as during dehydration processes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, lichenized fungi, rock-inhabiting microcolonial fungi (RIF) and yeasts are considered rock specialists and are commonly retrieved from different rock substrates (e.g. Fanelli et al 2021, Choe et al 2021, Ertekin et al 2021). Yet, whether a consistent membership of these rock-associated fungi exists across different biomes and continents is still undetermined .…”
Section: Introductionmentioning
confidence: 99%